Exploring the Impact of Qowa'id Nahwu Mastery on Insha' Ability: A Correlation Study: Eksplorasi Dampak Penguasaan Qowa'id Nahwu pada Kemampuan Menulis Insha': Studi Korelasi - Rahmawati, Dita Wahyuning; Fauji, Imam (Indonesian Journal of Education Methods Development, 2023)
This study investigates the influence of Qowa'id Nahwu mastery on the insha' (composition) ability of second-level students at Ma'had Umar bin Al-Khattab, Sidoarjo. Employing a quantitative non-experimental correlation approach, data analysis involved correlation tests between the mastery of qowa'id nahwu as the independent variable and the insha' ability as the dependent variable. The findings underscore a significant positive correlation (r = 0.685, p < 0.001) between qowa'id nahwu mastery and insha' ability, indicating a pronounced influence of grammatical competence on composition skills. The implications of these findings resonate across educational settings, emphasizing the importance of strengthening qowa'id nahwu understanding to enhance students' written expression proficiency. Highlights: The study examines the relationship between Qowa'id Nahwu mastery and insha' ability among second-level students. A significant positive correlation (r = 0.685, p < 0.001) highlights the impact of grammatical competence on composition skills. Strengthening qowa'id nahwu understanding is crucial for enhancing students' written expression proficiency. Keywords: Qowa'id Nahwu, Insha' Ability, Correlation Study, Second-Level Students, Educational Implications